Cost-effectiveness Analysis Comparing Conventional, Hypofractionated, and Intraoperative Radiotherapy for Early-Stage Breast Cancer - Deshmukh, Ashish A; Shirvani, Shervin M; Lal, Lincy; Swint, J Michael; Cantor, Scott B; Smith, Benjamin D; Likhacheva, Anna (JNCI : Journal of the National Cancer Institute, 2017)
Early-stage breast cancer is among the most prevalent and costly malignancies treated in the American health care system. Adjuvant radiotherapy after lumpectomy represents a substantial portion of breast cancer expenditures. The relative value of novel radiotherapeutic approaches such as intraoperative radiotherapy (IORT) and hypofractionated whole breast irradiation (HF-WBI) compared with conventionally fractionated whole breast irradiation (CF-WBI) is unknown. Therefore, we used prospectively collected outcomes from randomized clinical trials (RCTs) to compare the cost-effectiveness of these approaches. We constructed a decision-analytic model that followed women who were treated with lumpectomy for early-stage breast cancer. Recurrence, mortality, complication rates, and utilities (five-year radiation-associated quality of life scores), were extracted from RCTs. Costs were based on Medicare reimbursement rates. Cost-effectiveness from societal and health care sector perspectives was estimated considering two scenarios-the first assumes that radiation-associated disutility persists five years after treatment, and the second assumes that disutility discontinues. Lifetime outcomes were summarized using incremental cost-effectiveness ratios (ICERs). Deterministic and probabilistic sensitivity analyses evaluated the robustness of the results. HF-WBI dominated CF-WBI (ie, resulted in higher quality-adjusted life-years [QALYs] and lower cost) in all scenarios. HF-WBI also had a greater likelihood of cost-effectiveness compared with IORT; under a societal perspective that assumes that radiation-associated disutility persists, HF-WBI results in an ICER of $17 024 per QALY compared with IORT with a probability of cost-effectiveness of 80% at the $100 000 per QALY willingness-to-pay threshold. If radiation-associated disutility is assumed to discontinue, the ICER is lower ($11 461/QALY), resulting in an even higher (83%) probability of relative cost-effectiveness. The ICER was most sensitive to the probability of metastasis and treatment cost. For women with early-stage breast cancer requiring adjuvant radiotherapy, HF-WBI is cost-effective compared with CF-WBI and IORT.